Basement oil of sedimentary basins is an alternative of “shale” scenario of global FEC development (West Siberia as an example) - A.I. Timurziev (Геофизический журнал, 2019)
Concepts on structure, composition and oil presence of the West Siberia basement are considered in the paper. Information on oil and gas presence in the basement of the world is presented, its inexhaustible potential is unveiled. Critical analysis of concepts on oil genesis in the basement of West Siberia as well as in White Tiger deposit has been given on the basis of the theory of organic origin and descending oil migration while producing the deposits. Principles of alternative inorganic image of the “basement oil” based on the ideas of the “Deep oil” are discussed. Problems of formation of West Siberia oil deposits have been considered in an aspect of history of West Siberia development; features of structure and search and exploration methods of occurrences in basement fissure collectors; geological signs and criteria of mapping basement displacements of channels of deep oil vertical migration localized on the bodies. “Complex Program for development of the West Siberia basement on the grounds of HC deep genesis” has been proposed. Basement oil of sedimentary basins is considered as a primary alternative of a “shale” scenario of the world FEC development. Alternative scenario of development and renewal of the world FEC from inevitable stagnation suggests immediate change from organic paradigm of oil-gas geology of Gubkin—Vassoyevich—Kontorovich to its antagonistic-alternative inorganic theory of Mendeleev—Kudryavtsev—Porfiriev. Otherwise, no “shale revolution” and alternative energetics will help the world fuel complex to avoid energetic crisis and society to come back to “stone” (coal) age, before coming to the next level of hydrogen energy.